2013
DOI: 10.3945/ajcn.112.045583
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of whole grain reduces risk of deteriorating glucose tolerance, including progression to prediabetes

Abstract: A higher intake of whole grain is associated with decreased risk of deteriorating glucose tolerance including progression from normal glucose tolerance to prediabetes by mechanisms likely tied to effects on insulin sensitivity. Effect modifications by TCF7L2 genetic polymorphisms are supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 26 publications
6
80
0
Order By: Relevance
“…Twelve studies (13 publications) [6, 810, 2633, 35] in addition to the EPIC-InterAct Study were included in the analysis (30,224 cases and 455,563 participants). One of the studies [32] was only included in the analysis of the highest vs the lowest intake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies (13 publications) [6, 810, 2633, 35] in addition to the EPIC-InterAct Study were included in the analysis (30,224 cases and 455,563 participants). One of the studies [32] was only included in the analysis of the highest vs the lowest intake.…”
Section: Resultsmentioning
confidence: 99%
“…This is possible in this context as some other studies have used more imprecise measures, such as self-reported BMI, and could therefore have more issues with residual confounding. Of 11 studies of cereal fibre that adjusted for BMI, all six studies with self-reported weight and height reported inverse associations [810, 26, 31, 33], while only two [6, 28] out of five of the studies [6, 28, 29, 35] (including EPIC-InterAct) with measured weight and height reported significant inverse associations. However, data for other fibre types and total fibre do not appear to vary by whether weight and height was measured or self-reported, so chance can also not be excluded as an explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Through meta-analysis, fasting blood glucose indicated 18 mg/dL lower blood glucose, l32 mg/dL lower total cholesterol, and 28 mg/dL lower LDL-cholesterol in people who consumed whole grains compared to those who did not. Wirström et al (27) studied 5,477 people aged 35-56 y (males 2,297, females 3,180) for 8-10 y and found that people who consumed 59.1 g of whole grain per day had a 22% lower risk of glucose metabolism disorder than those who ate less than 30.6 g a day when the data were adjusted for age, family history of DM, physical activity, smoking, education and blood pressure. Hu et al (10) reviewed 4 papers and reported about 2 times higher risk of DM in people who ate WR every day than in those who did not eat it every day.…”
Section: Discussionmentioning
confidence: 99%
“…7 Conversely, high intake of whole grain is connected with reduced risk of developing glucose tolerance typical of pre-diabetic conditions. 8 Moreover, dietary habits can also contribute to the risk of contracting colorectal malignancy. 9,10 Actually, there is concern among health professionals of a likely connection between high consumption of red and processed meat and colorectal carcinoma incidence, although no mechanistic model as yet has been demonstrated.…”
Section: Dietary Surveys -Consumption Patterns and Healthmentioning
confidence: 99%